2012
DOI: 10.4103/0972-0707.101882
|View full text |Cite
|
Sign up to set email alerts
|

Dentinal hypersensitivity: A comparative clinical evaluation of CPP-ACP F, sodium fluoride, propolis, and placebo

Abstract: Background:Dentine hypersensitivity is a transient condition that often resolves with the natural sclerotic obturation of dentinal tubules. A potent topically applied in-office desensitizing treatment is indicated as the choice of treatment when dentine hypersensitivity is localized to one or two teeth.Aim:The present study aimed to evaluate and compare the clinical efficiency of CPP-ACP F, sodium fluoride, propolis, and distilled water that was used as placebo in treating dentinal hypersensitivity.Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 11 publications
4
27
0
5
Order By: Relevance
“…Restrepo et al and Ozgul et al reported the reduction of dental hypersensitivity in MIH‐affected teeth after application of fluoride varnish. These results are similar to those found by other authors in patients without MIH, who reported a decrease in dental hypersensitivity after the use of fluoride varnishes. Thus, fluoride varnish treatments may be considered a therapeutic option in cases of MIH‐related dental hypersensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…Restrepo et al and Ozgul et al reported the reduction of dental hypersensitivity in MIH‐affected teeth after application of fluoride varnish. These results are similar to those found by other authors in patients without MIH, who reported a decrease in dental hypersensitivity after the use of fluoride varnishes. Thus, fluoride varnish treatments may be considered a therapeutic option in cases of MIH‐related dental hypersensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…The present results agree with other clinical studies in which the application of concentrated fluoride to exposed buccal dentin surfaces was effective in reducing hypersensitivity, as demonstrated by the increased resistance of dentin to decalcification and by the precipitation of calcium fluoride crystals in exposed dentinal tubules (14,16). However, Umberto et al (14) observed a greater efficacy of GaAlAs laser radiation when compared to NaF gel.…”
Section: Discussionsupporting
confidence: 63%
“…The high calcium availability provided by CLP, a novel remineralization agent, was attributed to its high solubility and calcium stabilization by random formation of metastable complexes of calcium ions with lactate and phosphate ions. Currently, remineralizing agents like NovaMin™ (bioactive glass containing calcium sodium phosphosilicate) [27,28], Recaldent™ (CPP-ACP casein phosphopeptide-amorphous calcium phosphate) [27,29], Enamelon ® (containing stannous fluoride along with calcium and phosphate ions) [30] were utilized as desensitizing agents. Analogous mechanism to these remineralizing agents is expected to provide the same relief to DH as CLP pastes.…”
Section: Discussionmentioning
confidence: 99%